Quinaluiza Jaguaco Franklin Marcelo (2022); Estudio de tres métodos de control de candidatus liberibacter solanacearum en seis ecotipos de Tomate de Árbol solanum betaceum en etapa de desarrollo, Cusubamba – Cotopaxi 2021. - Quinaluiza Jaguaco, Franklin Marcelo (2022)
This research aimed to detect the best preventive method in which PCR results acquired from a molecular biology laboratory were taken into account in the Carrillo sector, Cusubamba parish, Salcedo canton, 2,981 meters above sea level. The ecotype capable of presenting resistance and tolerance to the permanent disease of tomato was identified through a multivariate analysis of principal components and clusters. A mínimum population of the vector agent Bactericera cockerelli was evidenced, obtained from weekly monitoring, which influenced the rotation of active ingredients, generating a qualified environmental impact through the Leopold Matrix. Negative PCR results were obtained in the three control methods implemented with gentamicin sulfate and oxytetracycline hydrochloride from the plant nursery and in the field (C), only in the field (B1) and sentinel (without chemicals against bacterium) (B0), so three ecotypes from Belisario Quevedo without disease, Atuntaqui, and Nabuzo, were the ones that resisted the disease in the sector, controlling the vector in the development stage with different molecules such as imidacloprid, azoxystrobin, tridemorph, abamectin, pyridaben, formetanate, fipronil, profenofos and thiamethoxan, causing an unfavorable environmental impact during this stage on tree-tomato. The tolerant ecotypes detected in the research should be implemented to reduce the detrimental effect of the vascular pathogen, including a random location of adherent traps to create greater control over the vector agent, preventing the transmission of Candidatus Liberibacter solanacearum to the crop.